PEMBUATAN FLAKES DENGAN PENCAMPURAN TEPUNG UBI JALAR KUNING (Ipomoea Batatas L.) DAN TEPUNG JAGUNG LOKAL VARIETAS ’MANADO KUNING’ (Zea Mays L.) - Repi, Keysi; Langi, Tineke M.; Taroreh, Mercy (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
ABSTRACTThe purpose of this study was to determine the formula for the mixture of yellow sweet potato flour and Manado yellow corn flour which was favored by panelists and determine the physicochemical properties of flakes. This research was carried out using a completely randomized design, consisting of 4 treatment levels and 3 repetitions: A (70% yellow sweet potato flour: 30% Manado yellow corn flour), B (50% yellow sweet potato flour: 50% Manado corn flour yellow), C (30% yellow sweet potato flour: 70% yellow Manado corn flour), D (10% yellow sweet potato flour: 90% Manado yellow corn flour). The formula for mixing in making yellow sweet potato flour flakes and local Manado yellow varieties of corn flour preferred by panelists was obtained from 30% yellow sweet potato flour and 70% local manado yellow corn flour with a preference for color having a neutral value, on aroma having like indigo , the feeling of having a value of liking, and crispness has a value rather like the nutrient content of water content 4.04%, ash content 3.53%, protein content 8.5%, fat content 3.58%, and carbohydrates 80.36% . Keywords: flakes, yellow sweet potato, Manado yellow corn varieties